Innovation of Colostomy Appliance from Deproteinised Natural Rubber (DPNR) - Wanitsuwan, Worrawit; Krainara, Pawan; Kalkornsurapranee, Ekwipoo; Srisintorn, Wisarut; Pichayakorn, Wiwat; Taweepreda, Wirach; Wongputtisin, Pairote; Wannawong, Somporn (International Journal of Innovative Research in Medical Science, 2019)
Background and Objectives: In Thailand, the Colorectal cancer incidence rate is 127.7 per 100,000 for men and 125.5 per 100,000 for women. Twenty percent of these patients have a permanent or temporary colostomy that needs colostomy flange. The colostomy flanges that are available in Thailand are imported and are expensive. Thailand is an agricultural country and is the leading natural rubber producer and exporter. Flange made within the country would cost significantly less than the imported ones. Nevertheless, the safety standard is the main point that we considered. Material and methods: This study is an experimental prospective non-randomized control trial study at Songklanagarind Hospital. The study was approved and monitored by the ethical committee of Songklanagarind Hospital. Thailand Institute of Scientific and Technological Research (TISTR) approved the animal phase. Then, the volunteer phase was performed to conduct the best one of the material formulas for colostomy flange. Result: Fresh latex has 16.66% dermatitis and no anaphylaxis. Block latex and concentrated latex has the same allergic symptoms (13.1% dermatitis) but Block latex show a lower rate of other symptoms including itch and hyperpigmentation. Block latex was selected to produce Deproteinised Natural Rubber (DPNR). Three Deproteinised Natural Rubbers (DPNR) were achieved. Rubber formula 2 causes the lowest allergic symptoms; there is no anaphylaxis and only 0.5% dermatitis. Conclusion: Rubber formula 2 is the lowest prevalence of latex allergy in this study and is a lower prevalence compared to the previous study. It is suggested that Rubber formula 2 is safe to be the material for producing a colostomy flange. However, clinical trial and data must be collected during the patient phase trail.